Validation of Instrumented Insoles for Measuring Height in Vertical Jump - Martínez-Martí, F.; González-Montesinos, J. L.; Morales, D. P.; Santos, J. R. F.; Castro-Piñero, J.; Carvajal, M. A.; Palma, A. J. (International Journal of Sports Medicine, 2016)
The purpose of this study was to validate a new instrumented insole called ECnsole for measuring flight time during vertical jump performance. 66 participants performed 3 different jump tests (squat jump, countermovement jump and Abalakov jump) twice with flight times determined using an instrumented insole composed of 4 pressure sensors (PreECnsole) and an accelerometer sensor (AccECnsole), a laser platform (Sport Jump System Pro), and a high-speed motion capture system (HSC); the latter 2 systems are considered as reference methods. One-way analysis of variance (ANOVA), simple linear regression, and the Bland-Altman method were used to assess validity. Regardless of the jump test performed, the ECnsole system showed a systematic bias close to 0 and a low random error (average random error: ±2.8 cm; ±3.1 cm PreECnsole and AccECnsole vs. HSC system respectively and ± 2.3 cm; ±2.9 cm PreECnsole and AccECnsole vs. SJS system respectively). The associations between PreECnsole and AccECnsole with the HSC were very high (R2=0.967 and 0.958 respectively). Furthermore, the associations between PreECnsole and AccECnsole with the SJS were very high (R2=0.978 and 0.966 respectively) as well. Therefore, the ECnsole system can be considered an alternative method for measuring jump height during vertical jump performance.
Keywords: biomechanics; insoles; vertical jump; force sensors; accelerometer